PENGARUH PELAPISAN BENIH (SEED COATING) DAN CEKAMAN KEKERINGAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L.) - Nisfiyah, Lailatin; Rahman, Fahmi Arief; Supriyadi, Slamet (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Part of the dry land in Madura developed from parent material, namely sand sediments which have a low organic matter content. This study aimed to determine differences in the effectiveness of corn seed coating materials from bentonite, biochar, lignite, and biochar compost on the growth and yield of maize (Zea mays L.) under drought stress conditions. This study was conducted at the Integrated Laboratory and screen house of the Faculty of Agriculture, University of Jember, using a completely randomized design. The treatments tested in this study comprised two factors. The first factor was the treatment of coating materials, namely C0 = without coating (control), C1 = bentonite coating, C2 = biochar coating, C3 = lignite coal coating, and C4 = biochar compost coating. The second factor is the level of drought stress, namely K0 = control (100% KL moisture), K1 = Light stress (80% KL moisture), K2 = moderate stress (60% KL moisture), and K3 = severe stress (40% KL moisture). The results showed that the combination of seed coating agent treatment and drought stress had a significant effect on the parameters of plant height, number of leaves, leaf area, age of male and female flowers, cob length, cob diameter without husks, biomass dry weight, and production potential per hectare. The coal coating material and light drought stress 80% KL (C3K1) was the best combination of seed coating and drought stress treatment.